1982
DOI: 10.1007/bf01870471
|View full text |Cite
|
Sign up to set email alerts
|

Radio-frequency rectification in electrogenic and nonelectrogenic cells ofChara andNitella

Abstract: Summary. Electrogenic cells of Chara braunii and Nitella flexiliswere placed in a pulse-modulated radio-frequency electric field of up to 6000 V/re. Their vacuolar resting potentials were found to experience submillivolt depolarizing offsets (typically 140 ~tV at 250 kHz) which were relatively independent of temperature, increased linearly with resting potential from a zero near -210 mV, and had a cutoff (putatively due to ion transit times) near 5 MHz.By contrast, nonelectrogenic cells experienced hyperpolari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…There has been some debate about whether fusicoccin has any effect upon charcean algae. Marr6 (1978) found a "small but significant" effect of FC upon H + extrusion in a species of Chara and Barsoum and Pickard (1982)found that fusicoccin hyperpolarized "nonelectrogenic" internodes of Chara braunii and Nitellaflexilis. Lucas and Ferrier (1980) concluded that FC does not cause an active H + extrusion in Chara corallina internodes, but there was a small effect of FC on carbon uptake in these ceils.…”
Section: Discussionmentioning
confidence: 99%
“…There has been some debate about whether fusicoccin has any effect upon charcean algae. Marr6 (1978) found a "small but significant" effect of FC upon H + extrusion in a species of Chara and Barsoum and Pickard (1982)found that fusicoccin hyperpolarized "nonelectrogenic" internodes of Chara braunii and Nitellaflexilis. Lucas and Ferrier (1980) concluded that FC does not cause an active H + extrusion in Chara corallina internodes, but there was a small effect of FC on carbon uptake in these ceils.…”
Section: Discussionmentioning
confidence: 99%
“…Any asymmetric ion transport process in a cell, for example, the transit of an ion through a membrane ion channel, could exhibit diode-like behavior, and at sufficiently low frequencies the electric properties of the membrane would appear nonlinear. For example, Barsoum and Pickard [36] showed that the cell membrane in electrogenic cells of Chara braunii and Nitella flexilis showed rectification properties at frequencies up to 10 MHz, limited by ion transit times through the membrane. Rectification by ion channels has been observed at higher RF frequencies at intense field levels for artificial channels in bilipid membranes by Ramachandran et al [37].…”
Section: Demodulation Of Modulated Rf Signalsmentioning
confidence: 98%
“…(1) For the nonelectrogenic cells studied by Pickard and Barsoum [1981] from 250 kHz to the putative transit time cutoff, the value of 2 (1 -6) was roughly 1.8. For the electrogenic cells reported by Barsoum and Pickard [1982] its value over the range 25-250 kHz was roughly 1.7. The capacitance data of Haydon et al [I9801 for squid axon membrane yielded a 6 of roughly 0.4 for the range 50-300 kHz.…”
Section: Acknowledgmentsmentioning
confidence: 93%